Front-Page Girls : Women Journalists in American Culture and Fiction, 1880-1930 - Lutes, Jean Marie (Cornell University Press, 2018)
The first study of the role of the newspaperwoman in American literary culture at the turn of the twentieth century, this book recaptures the imaginative exchange between real-life reporters like Nellie Bly and Ida B. Wells and fictional characters like Henrietta Stackpole, the lady-correspondent in Henry James's Portrait of a Lady. It chronicles the exploits of a neglected group of American women writers and uncovers an alternative reporter-novelist tradition that runs counter to the more familiar story of gritty realism generated in male-dominated newsrooms. Taking up actual newspaper accounts written by women, fictional portrayals of female journalists, and the work of reporters-turned-novelists such as Willa Cather and Djuna Barnes, Jean Marie Lutes finds in women's journalism a rich and complex source for modern American fiction. Female journalists, cast as both standard-bearers and scapegoats of an emergent mass culture, created fictions of themselves that far outlasted the fleeting news value of the stories they covered.Front-Page Girls revives the spectacular stories of now-forgotten newspaperwomen who were not afraid of becoming the news themselves--the defiant few who wrote for the city desks of mainstream newspapers and resisted the growing demand to fill women's columns with fashion news and household hints. It also examines, for the first time, how women's journalism shaped the path from news to novels for women writers.